Gene flow and Andean uplift shape the diversification of Gasteracantha cancriformis (Araneae: Araneidae) in Northern South America (2018)
The Andean uplift has played a major role in shaping the current Neotropical biodiversity. However, in arthropods other than butterflies, little is known about how this geographic barrier has impacted species historical diversification. Here, we examined the phylogeography of the widespread color polymorphic spider Gasteracantha cancriformis to evaluate the effect of the northern Andean uplift on its divergence and assess whether its diversification occurred in the presence of gene flow. We inferred phylogenetic relationships and divergence times in G. cancriformis using mitochondrial and nuclear data from 105 individuals in northern South America. Genetic diversity, divergence, and population structure were quantified. We also compared multiple demographic scenarios for this species using a model-based approach (Phrapl) to determine divergence with or without gene flow. At last, we evaluated the association between genetic variation and color polymorphism. Both nuclear and mitochondrial data supported two well-differentiated clades, which correspond to populations occurring on opposite sides of the Eastern cordillera of the Colombian Andes. The final uplift of this cordillera was identified as the most likely force that shaped the diversification of G. cancriformis in northern South America, resulting in a cis- and trans-Andean phylogeographic structure for the species. We also found shared genetic variation between the cis- and trans-Andean clades, which is better explained by a scenario of historical divergence in the face of gene flow. This has been likely facilitated by the presence of low-elevation passes across the Eastern Colombian cordillera. Our work constitutes the first example in which the Andean uplift coupled with gene flow influenced the evolutionary history of an arachnid lineage. © 2018 The Authors. Ecology and Evolution published by John Wiley & Sons Ltd.